THE EFFECT OF CONCRETE DOPING USING PALM PALM BOILER ASH AND SUPERPLASTICIZER ON THE STRENGTH OF K-300 CONCRETE - Surya Kurniawan Hutabarat; Nurdin Siregar (Universitas Negeri Medan, 2026)
Concrete is a favorite reinforcement material that is commonly used in Indonesia because it has superior properties compared to other materials. Some of the advantages of concrete include economical prices, cheap manufacturing processes, heat resistance, strong strength and materials that are easy to obtain. Every year the number.The population in Indonesia is increasing, which causes high demand for building materials, in this case there is a shortage of mixed materials for making concrete. This concrete synthesis research was carried out to determine the effect of a mixture of palm oil boiler ash and superplasticizer on concrete strength, water absorption capacity and concrete morphology. The concrete is made in the shape of a cube with dimensions of 15 cm x 15 cm x 15 cm according to the SNI 7394(2008) k-300 standard. The mixture variations used are ABKS 100 Mesh (0%, 1.5%, 3%, 4.5% and 7.5%) and superplasticizer 0% and 2%. After a period of 28 days the concrete was tested using the compressive strength test method using existing procedures. The highest compressive strength was in a mixture composition of 7.5 ABKS and 2% SP of 34.55 Mpa and the lowest compressive strength was in concrete without a mixture of 20. 88 Mpa. With the highest water absorption capacity of 0.52% in the unmixed concrete variation and the lowest in the 7.5 ABKS and 2% SP mixture of 0.27%. EDX analysis results show that unmixed concrete contains the highest element of 32.49 % Calcium (C) And in the highest quality concrete the mixture of boiler ash and superplasticizer with the highest element of Silica (Si) is 20.55%. The compressive strength results exceed the SNI provisions that have been set. The higher the addition of the mixture composition, the higher the compressive strength concrete and the concrete's absorption capacity is getting lower.